Effects of acids pre-treatment on the microbial fermentation process for bioethanol production from microalgae - Phwan C.K.; Chew K.W.; Sebayang A.H.; Ong H.C.; Ling T.C.; Malek M.A.; Ho Y.-C.; Show P.L. (BioMed Central Ltd., 2023)
Acetic acid; Algae; Energy utilization; Ethanol; Fermentation; Microorganisms; pH; Process control; Sulfuric acid; Bio-ethanol production; Carbohydrate content; Commercial productions; Micro-algae; Microbial fermentation process; Pre-Treatment; Pretreatment methods; Reducing sugars; Bioethanol; biomass; carbohydrate; chemical bonding; concentration (composition); ethanol; fermentation; microalga; microbiology